Compact Fano-Type Liquid Metamaterial Resonator for High-Precision Temperature Sensing - Chen, Haotian (Frontiers in Materials, 2022)
In this paper, a liquid metal mercury (Hg) based high quality-factor (Q-factor) liquid electromagnetic metamaterial unit, the Hg Fano resonator, is designed for the high-precision temperature sensing application. Such Fano resonance in the Hg-resonator is excited by the microstrip-line coupling and the resonance frequency is sensitive to the background temperature changings. Based on the high Q-factor and the temperature-sensitive features of Hg-Fano resonator, the high-precision temperature sensing performance is discussed and achieved, with numerical and experimental demonstrations. The experimental sensitivity of 11.7 MHz/°C and figure-of-merit (FOM) of 0.4/°C are obtained. The proposed compact Hg-Fano resonator based sensor can be widely used for the wireless temperature sensing area.